Vachellia erioloba (camel thorn) and microbial interactions - Van Aswegen, Sunet (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2018)
Vachellia erioloba (camel thorn) is one of South Africa's economically important tree species and therefore requires further investigation to improve its health and growth. Beneficial soil microbes have positive effects on plants through various mechanisms such as nitrogen fixation, phosphate solubilisation, indole acetic acid and siderophore production and biofilm formation. These traits enhance plant growth and protect the host plant against parasitic organisms that are present in soil. The arbuscular mycorrhizal (AM) fungi are well known for their beneficial symbiotic effects on host plants. The objective of this study was to determine the role of AM fungi and associated beneficial rhizobacteria in improving the growth of V. erioloba seedlings. Soil and root samples were collected from a farm in the Northern Cape, South Africa. Fifty-seven bacterial cultures were isolated from the soil and tested for plant growth promoting characteristics. Fourteen isolates showing at least four beneficial traits were molecularly identified using the GenBank database. The AM fungal and bacterial populations in the soil samples were assessed using Illumina sequencing. Sequences were identified using the MaarJAM and GenBank databases, respectively. Three separate pot trials were conducted to determine; 1) the effects of cadmium (Cd) on seedling growth; 2) the individual effects of three selected bacterial isolates and AM fungi alone and combined on seedling growth, and 3) the combined effects of the selected bacteria on AM fungal inoculated and uninoculated seedlings. Of the fourteen isolates the Enterobacter genera was the dominant species identified, with Acinetobacter, Pantoea and Bacillus each having one isolate. All were described as plant growth promoting rhizobacteria. One isolate from each genus, excluding Pantoea, was used in the pot trials. Three genera were identified in the AM fungal population that was assessed, namely Ambispora, Paraglomus and Glomus with Ambispora being the dominant genus. The bacterial population assessed showed a high diversity of bacteria from the Actinobacteria phylum being the dominant group. The results of the heavy metal pot trial showed that the symbiotic relationship between the seedlings and AM fungi increased the seedlings' health and growth during heavy metal stress. The combination of bacteria and AM fungi increased growth parameters in all the inoculated seedlings, but not when compared to uninoculated seedlings indicating a possible competition for nutrients. The results were influenced by the presence of a nematode, which was suspected to have been seed borne. Further investigations on these interactions are required. Inoculation of AM fungi and selected PGPR is recommended for V. erioloba seedling production.
Keywords: Vesicular-arbuscular mycorrhizas; Cadmium; Rhizobacteria; Plant growth-promoting rhizobacteria; Acacia erioloba